Estimating the Size of External Effects of Energy Subsidies in Transport and Agriculture - Commander, Simon (World Bank Group, Washington, DC, 2015)
It is widely accepted that the costs of underpricing energy are large, whether in advanced or developing countries. This paper explores how large these costs can be by focussing on the size of the external effects that energy subsidies in particular generate in two important sectors—transport and agriculture—in two countries in the Middle East and North Africa, the Arab Republic of Egypt (transport) and the Republic of Yemen (agriculture). The focus is mainly on the costs associated with congestion and pollution, as well as the impact of underpriced energy for depletion of scarce water resources, including through crop selection. Quantifying the size of external effects in developing countries has received relatively little analytical attention, although there is a significant body of literature for developed countries. By building on earlier research, as well as employing the United Nations ForFITS model, the paper provides indicative estimates of the external costs of energy subsidies, as manifested in congestion and pollution. The estimates using simulations indicate that these costs could be materially reduced by elimination or reduction of energy subsidies. The paper also describes the impact of energy subsidies on water consumption in a region where water resources are particularly limited. The findings provide further evidence of the adverse and significant consequences of subsidizing energy.